Evaluation of Systemic Inflammatory Indices of Earthquake Victims After the 6 February Kahramanmaraş Earthquake - Merve Erçelik; Önder Öztürk; Tutku Aydın; Hilal Türkmen Kaya (Thoracic Research and Practice)
OBJECTIVE: Earthquakes cause many people to lose their lives, get injured and leave their homes. Earthquakes constitute a serious risk factor for physical and mental diseases primarily due to traumatic environmental experiences. Systemic inflammation indices are used to determine prognosis in many diseases. This study aims to investigate the effects of the distance of earthquake victims from the epicentre of the earthquake, whether trapped under debris, and their psychological distress on the systemic inflammatory indices. MATERIAL AND METHODS: Systemic inflammatory indices were retrospectively calculated for all earthquake victims. Questionnaires were evaluated prospectively among earthquake victims who volunteered. RESULTS: The systemic inflammation values were aggregate index of systemic inflammation (AISI) median 351.5, systemic inflammation response index (SIRI) median 1.30, and systemic inflammation index (SII) median 677.4. Although the number of earthquake survivors under rubble was lower than the number of earthquake survivors not under rubble, AISI (P = 0.001), SIRI (P = 0.03), and SII (P = 0.002) were found to be statistically significantly higher in those under rubble. Depression scores (mean, 37.8) and anxiety scores (mean, 43.6) were compatible with moderate and severe categories. There was a significant relationship between AISI (P = 0.018) and SIRI values (P = 0.05) and depression outcome. Similarly, there was a statistically significant relationship between anxiety outcome and SII values (P = 0.002). CONCLUSION: A significant correlation was found between the physical and psychological trauma experienced by the earthquake victims and the high level of systemic inflammatory indices. Rehabilitation and close follow-up of the earthquake victims are of great importance given that systemic inflammation is one of the long-term health effects of earthquakes.